Pelvic Pathologies in Primary Infertility: A Diagnostic Laparoscopy Study of 106 Patients - Shabnam, Zarina Khan, Parveen Azam, Shahida Karamat, Qamoos Razzaq, Jamshed Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the frequency of pelvic pathologies diagnosed via diagnostic laparoscopy in patients with primary infertility. Methods: A retrospective study was conducted on 106 women diagnosed with primary infertility who underwent diagnostic laparoscopy between September 2022 to August 2023. Clinical records, laparoscopy findings, and patient outcomes were reviewed. The most common pelvic pathologies identified were recorded and analyzed. Results: Among the 106 patients, the most frequent pelvic pathologies included tubal occlusion (30%), endometriosis (25%), pelvic adhesions (18%), and uterine anomalies (10%). A significant correlation was found between the presence of endometriosis and tubal occlusion (p<0.05). Additionally, adhesions were most commonly associated with previous pelvic surgeries or infections. Conclusion: Diagnostic laparoscopy is a valuable tool for identifying pelvic pathologies in primary infertility. Tubal factors and endometriosis are the most common causes, with significant implications for fertility management. Keywords: Primary infertility, diagnostic laparoscopy, pelvic pathologies, tubal occlusion, endometriosis, adhesions, uterine anomalies.